Powering Down Hospitality Through a Policy-Driven, Case-Based and Scenario Approach - Angeliki N. Menegaki (Energies)
The hospitality sector is a substantial energy consumer, driven by the demands of heating, cooling, lighting and guest amenities. This study explores energy consumption patterns across different hotel types, highlighting luxury hotels’ higher usage compared to mid-range and budget establishments. Key energy drivers include HVAC systems, lighting and hot water. Legislative frameworks, such as the Paris Agreement, the Sustainable Development Goals and European Union directives, set ambitious energy efficiency and emissions targets for the sector. Through case studies on Marriott, Hilton and Hotel Verde, the study demonstrates effective energy-saving practices, including LED lighting, smart HVAC systems and renewable energy integration, which can reduce energy use by 10–20%. The findings show the dual benefits of these measures, which enhance environmental sustainability and reduce operational costs. By adopting these practices, hotels can align with evolving regulatory standards and cater to the growing demand for eco-friendly accommodations.